2014
DOI: 10.1002/pc.22930
|View full text |Cite
|
Sign up to set email alerts
|

In situ polymerization, thermal, damping, and mechanical properties of multiwalled carbon nanotubes/polyisobutylene‐based polyurethane nanocomposites

Abstract: Despite the development of strong, durable, and cost efficient polyisobutylene-based polyurethane (PIBbased PU) materials has yet to be achieved. The well dispersion and maximum interfacial interaction between the nanofiller and the PIB-based PU at low loading have been scarcely studied. Here, the preparation of PIB-based PU nanocomposites with Multiwalled carbon nanotubes (MWCNTs) using a simple in situ polymerization method is reported. The thermogravimetric analysis tests show that MWCNTs significantly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The use of organoclay lead to the cell size reduction, however, uneven dispersion of the organoclay in the polyol solution was observed. While the incorporation of carbon nanotubes or graphenes in PUF has shown to improve its thermal, electrical, and mechanical properties , studies on their influence on acoustic damping properties are limited . A few studies reported the acoustic damping properties of PUF without correlation to its airflow resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organoclay lead to the cell size reduction, however, uneven dispersion of the organoclay in the polyol solution was observed. While the incorporation of carbon nanotubes or graphenes in PUF has shown to improve its thermal, electrical, and mechanical properties , studies on their influence on acoustic damping properties are limited . A few studies reported the acoustic damping properties of PUF without correlation to its airflow resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mechanical parameters affecting the performance of AF and PU, respectively, also affect the mechanical behavior and structural stability of AF-PU composites. Different relative densities and pore size are two main factors influencing mechanical behavior of AF [13][14][15][16][17][18][19] and the usual influence parameters on the absorbed mechanical energy of PU are frequency, temperature and vibration amplitude [20][21][22][23][24]. In order to understand what kind of AF-PU materials are the most suitable for applying hysteretic damping devices in seismic resistant buildings, we will investigate the damping capacity of AF-PU composites with different corresponding porosity and pore size under different cycling frequency, vibration amplitude, temperature aging and cycle numbers.…”
Section: Introductionmentioning
confidence: 99%
“…In various literature, several methods have been reported for the preparation of rubber‐based nanocomposites that include melt intercalation, [ 21 ] solution mixing, [ 22 ] and in situ polymerization. [ 23 ] The melt intercalation method due to the more direct, cost‐effective, environmentally friendly, and more industrially, has been greater used than other methods. In this method, the polymer is heated with the nanoparticles upstream of the polymer softening point and the nanoparticles are sheared into smaller ones.…”
Section: Introductionmentioning
confidence: 99%